2023
DOI: 10.1128/jb.00061-23
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of the F-Like Plasmid-Encoded TraN Isoforms with Their Cognate Outer Membrane Receptors

Abstract: Conjugation plays a central role in the spread of antimicrobial resistance genes among bacterial pathogens. Efficient conjugation is mediated by formation of mating pairs via a pilus, followed by mating pair stabilization (MPS), mediated by tight interactions between the plasmid-encoded outer membrane protein (OMP) TraN in the donor (of which there are 7 sequence types grouped into the 4 structural isoforms α, β, γ, and δ), and an OMP receptor in the recipient (OmpW, OmpK36, OmpA, and OmpF, respectively)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The bacteria nanobody display library (100 ng) was then transformed into the E. coli MG1655 ΔompW strain via electroporation. We selected the Δ ompW strain to minimize the interactions between OmpW and TraN, as suggested by Low et al 21, 41 . The cells were harvested and resuspended in LB with 10% glycerol for storage at -80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria nanobody display library (100 ng) was then transformed into the E. coli MG1655 ΔompW strain via electroporation. We selected the Δ ompW strain to minimize the interactions between OmpW and TraN, as suggested by Low et al 21, 41 . The cells were harvested and resuspended in LB with 10% glycerol for storage at -80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Despite amino-acid differences in the extracellular region between OmpW KP and OmpW EC (Fig. 3c), where the tip of TraN R100-1 has been shown to bind (Low et al, 2023), binding of TraN R100-1 is not impaired between the two species. We previously reported that Ala142, which is conserved between OmpW KP and OmpW EC , acts as the minimum residue for specificity towards TraN R100-1 (Low et al, 2023); the equivalent residue in Citrobacter rodentium OmpW (OmpW CR ) is Asn142, which prevents R100-1 conjugation because of a steric clash with the tip of TraN R100-1 (Low et al, 2023).…”
Section: Comparison Of Ompw Kp With Ompw Ecmentioning
confidence: 95%
“…We previously reported that Ala142, which is conserved between OmpW KP and OmpW EC , acts as the minimum residue for specificity towards TraN R100-1 (Low et al, 2023); the equivalent residue in Citrobacter rodentium OmpW (OmpW CR ) is Asn142, which prevents R100-1 conjugation because of a steric clash with the tip of TraN R100-1 (Low et al, 2023). The N142A mutation in OmpW CR restored conjugation efficiency (Low et al, 2023).…”
Section: Comparison Of Ompw Kp With Ompw Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugative plasmids are well suited as delivery vectors for CRISPR nucleases or other genetic tools; they have a large coding capacity, they often encode CRISPR systems, , they encode factors that promote biofilm formation to enhance cell-to-cell contact and DNA transfer, they can carry antirestriction systems to promote resistance to restriction-modification systems, and they generally do not require a cellular receptor that would provide a mechanism for bacterial resistance, although some conjugative systems do require a receptor. , Conjugative systems initiate the unidirectional transfer of DNA from a donor to a recipient cell through the actions of the relaxase protein (MOB) that nicks DNA at a defined origin of the transfer sequence ( oriT ). , Subsequent interaction of the relaxosome with the type IV coupling protein (T4CP), mating pair formation, and type 4 secretion (T4SS) proteins catalyze DNA transfer to the recipient. Conjugative systems can exist as complete systems that are self-transmissible or as partial systems that are dependent on conjugative proteins encoded by other elements. Upon DNA transfer, some conjugative systems integrate into the chromosome as integrative conjugative elements (ICEs). Currently, the classification of conjugative systems is based on the identity of the MOB protein …”
Section: Introductionmentioning
confidence: 99%